Cationic cellulose and its interaction with chondroitin sulfate: rheological properties of the polyelectrolyte complex - Bierbrauer, Karina Lilian (2014)
This work describes the polyelectrolyte complexation between polyquaternium cellulose (PQ-10) and chondroitin 4-sulfate (C-4S), an important structural component of cartilages. The complex shows different behaviors with increasing concentrations of the polyanion. Initially, PQ-10/C-4S interaction forms a soluble, translucent hydrogel that reaches maximum viscosity at a sulfate carboxylate/quaternary ammonium molar ratio lower than 1. After that, the complex begins to aggregate until complete precipitation, and finally, at higher concentrations of C-4S, the resuspension of the aggregate is observed. Further addition of PQ-10 initiates new cycles of precipitation/resuspension for at least seven times. C-4S contains sulfates and carboxylates able to interact with quaternary ammonium of PQ-10. The results of a comparative study with polymers containing only carboxylate or sulfate to evaluate the influence of each group suggest that the phenomena observed involved, essentially, carboxylate groups.